The Effect of Individualized Instruction System on the Academic Achievement Scores of Students - Bahceci, Ferhat; Gurol, Mehmet (Hindawi Ltd, 2016)
A web-based learning portal offering individualized learning was developed by utilizing rule-based knowledge representation and artificial intelligence techniques of expert systems in order to reduce the uncertainties of learning to minimum and to construct an intelligent tutoring system. This portal offers individualized learning content based on the individual's level of cognitive knowledge. In order to determine the effects of the developed system on the student achievement, the system was tested in an 8-week-long study on the students of Software Engineering Department of Technology Faculty. The pretest-posttest control group experimental design was used in the study. The experimental group received education with Individualized Instruction Portal while the control group received education in traditional learning environment. Academic achievement test was used as the data collection tool. In order to test the research hypotheses, data obtained from the data collection tools were analysed in terms of frequency, percentages, and dependent-independent t-test with statistical software program. Based on the results, no significant differences were found between the groups in terms of the pretest. On the other hand, significant differences were found between experimental and control group in terms of the posttest. It was concluded that individualized learning portal had positive effect on the students' learning when used in combination with traditional learning environment.